2018
DOI: 10.1007/s11432-017-9284-4
|View full text |Cite
|
Sign up to set email alerts
|

Controllability analysis of multi-agent systems with switching topology over finite fields

Abstract: In this paper, we investigate the controllability problem of multi-agent systems with switching topology over finite fields. The multi-agent system is defined over finite fields, where agents process only values from a finite alphabet. Under leader-follower structure, one agent is selected as a leader for each subsystem. First, we prove that a multi-agent system with switching topology is controllable over a finite field if the graph of the subsystem is a spanning forest, and the size of the field is sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…It is shown that γ * almost reaches 1 at β = 1.2, compared with the corresponding value γ * = 0.4 under the AAT rule (i.e., β = π/2). Furthermore, Figures 7(b) and (c) denote the standard deviation curves of relative distance and velocity between the followers and the leader during each iteration, as defined in (8) and (9), respectively. At β = 1.2, the relative distance reaches 0, less than the corresponding values at both β = 1.2 and β = π/2.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that γ * almost reaches 1 at β = 1.2, compared with the corresponding value γ * = 0.4 under the AAT rule (i.e., β = π/2). Furthermore, Figures 7(b) and (c) denote the standard deviation curves of relative distance and velocity between the followers and the leader during each iteration, as defined in (8) and (9), respectively. At β = 1.2, the relative distance reaches 0, less than the corresponding values at both β = 1.2 and β = π/2.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Compared with the traditional centralized control-based network architecture, in a self-organizing network (SON) architecture, because each node can rely on local interactions with its neighbors to perform its communication tasks, the network's control signaling overhead can be greatly reduced by implementing the self-organizing mechanism. The swarm can be controlled by selecting one or more members as leaders to accomplish a number of specified tasks without requiring all members in the swam to maintain connections to the control center [9]. Obviously, the self-organizing control mechanism is very suitable for the drone group.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the proposed event-triggered finite-time controller design method has been verified by a numerical example. To further improve the proposed approach reliability and safety in practical applications, especially in networked control systems 43,44 and multiagent systems, [45][46][47][48] the problems of fading channels, [49][50][51] packet dropouts, 52,53 multiple input channels, 54 and cyber attacks [55][56][57] will be considered in our further work.…”
Section: Discussionmentioning
confidence: 99%
“…According to (60) and Cauchy-Schwarz inequality, the forward different for V n1 (k) can be derived as…”
Section: Stability Analysismentioning
confidence: 99%